Occurrence of autogeny in a population of Ornithodoros fonsecai (Acari: Argasidae) - Santiago, Ana Carolina Castro; Duarte, Leidiane Lima; Martins, Thiago Fernandes; Onofrio, Valeria Castilho; Nieri-Bastos, Fernanda Aparecida; Pacheco, Richard de Campos; Melo, Andréia Lima Tomé; Marcili, Arlei; Barros-Battesti, Darci Moraes [UNESP] (Elsevier, 2019)
Ornithodoros fonsecai is an argasid tick that is endemic to Brazil and has been described in the municipality of Bonito, state of Mato Grosso do Sul. Some specimens of this species were found in a cave in the municipality of Nobres, state of Mato Grosso. The specific identification of this population was confirmed by means of morphology and molecular biology. The mitochondrial 16S rDNA partial sequence of this species from Nobres has been deposited in GenBank (MK158949). The objective of this study was to elucidate the biology of O. fonsecai from Nobres, and to report autogeny in this tick population. Along three laboratory generations was observed molting of first nymphal instar to the second instar without feeding, a typical behavior of species included in the subgenus Alectorobius. The first generation (F1) presented five nymphal instars (N1 to N5), and most of adults emerged through molting of N5. The last nymphal instar of second generation (F2) was N4, but most of adults emerged from N3. In the third generation (F3) the last nymphal instar was N5, with most of the adults emerging from N4. In F2, some females (n = 20) originated from N3 began laying eggs without a blood meal. It was observed that those N3 fed twice before they molted to autogenic females. However, autogenic behavior occurred in relation to third generation females (F3) with specimens originating from N4 (n = 12) that were fed only once as nymphs. This behavior has already been reported as obligatory for the genera Otobius and Antricola, while it is facultative for one species of genus Argas and for four species of genus Ornithodoros. However, the present report provides the first record of facultative autogeny for a species of Ornithodoros in Brazil.
Keywords: Biology; Brazil; Ornithodoros fonsecai; Soft tick